MENCEGAH PERILAKU INTOLERAN MELALUI BUDAYA HASTHALAKU DI SOLO - Saudah Saudah; Ali Maksum; Khresna Bayu Sangka; Agung Nur Probohudono; Farid Sunarto; Didik Prasetyanto; Risca Dwi Jayanti (Jurnal Analisa Sosiologi, 2023)
The rise of intolerance behavior encourages various groups to take part in prevention. Solo Bersymphoni also participates in preventing intolerance through a learning model that upholds cultural identity. The cultural identity is contained in a local value called Hasthalaku or eight behaviors developed in the Adipangastuti School learning model. Adipangastuti School itself is a learning model that upholds the Hasthalaku Value in every school program activity with the aim of students becoming more tolerant and having a Hasthalaku cultural identity. The success of the Adipangastuti School program cannot be separated from the existence of social capital that plays a role in program development. Thus, through this study, researchers are interested in knowing how the role of social capital from Solo Bersymphoni in shaping the cultural identity of hasthalaku through the Adipangastuti School program in Solo. The research method in this article uses descriptive qualitative with Miles and Huberman data analysis techniques, and uses triangulation in obtaining data validity. The results of the study indicate that social capital plays a role in the development of Hasthalaku's cultural identity in the Adipangastuti school program so that it can be implemented in various schools in Central Java Province. The social capital in the development of the Adipangastuti School program is seen in the trust that forms the basis for establishing relationships and a sense of belonging to the program, the reciprocity that strengthens cooperation, and the ownership of networks that facilitate the formation of Hasthalaku cultural identity in an effort to prevent intolerance.Keyword: social capital,hasthalaku,  intolerance, Adipangastuti School, Solo Bersimfoni AbstrakMaraknya perilaku intoleransi mendorong berbagai kalangan untuk turut melakukan  pencegahan. Solo Bersimfoni turut melakukan pencegahan intoleransi melalui sebuah model pembelajaran yang menjujung identitas budaya. Identitas budaya tersebut dimuat dalam sebuah nilai-nilai lokal yang dinamakan sebagai Hasthalaku atau delapan perilaku yang dikembangkan dalam model pembelajaran Sekolah Adipangastuti. Sekolah Adipangastuti sendiri merupakan model pembelajaran yang menjunjung Nilai Hasthalaku pada setiap kegiatan program sekolah dengan tujuan siswa menjadi lebih toleran dan mempunyai identitas budaya hasthalaku. Keberhasilan program Sekolah Adipangastuti tidak terlepas dari adanya modal sosial yang turut berperan dalam pengembangan program. Sehingga, Melalui penelitian ini, peneliti tertarik untuk mengetahui bagaimana peran modal sosial dari Solo Bersimfoni dalam membentuk identitas budaya hasthalaku melalui program Sekolah Adipangastuti di Solo. Metode penelitian dalam artikel ini menggunakan kualitatif deskriptif dengan teknik analisis data miles dan huberman, serta menggunakan triangulasi dalam memperoleh keabsahan data. Hasil penelitian menunjukkan bahwa modal sosial menjadi hal yang berperan dalam pengembangan identitas budaya Hasthalaku dalam program sekolah adipangastuti hingga mampu diimplementasikan di berbagai sekolah di Provinsi Jawa Tengah. Modal sosial dalam pengembangan program Sekolah Adipangastuti tersebut terlihat dalam kepercayaan yang menjadi basis dalam menjalin hubungan dan rasa memiliki pada program, resiporisitas yang menguatkan kerjasama, dan kepemilikan jaringan yang mempermudah pembentukan identitas budaya Hasthalaku dalam upaya pencegahan intoleransi. Kata kunci: modal sosial, hasthalaku, intoleransi, sekolah adipangastuti, solo bersimfoni